Larangan Tentang Minuman Keras dalam Menyelenggarakan Kebaktian Berdasarkan Kitab Imamat 10:8-11 dan Implementasinya Bagi Gereja Masa Kini - Titi Noferita Lase; Yoseph Motty (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper explores the biblical prohibition of alcohol in worship, as described in Leviticus 10:8-11, and its application for churches today. The passage in Leviticus highlights God’s instruction to Aaron and his sons regarding the restriction on drinking alcohol while carrying out priestly duties. The article examines the theological and ethical significance of this command and discusses its implications for modern Christian worship practices. The study highlights the need for reverence and purity in worship and makes connections to current concerns like substance abuse and spiritual discipline within church communities. The paper concludes by offering practical guidance for churches to maintain holiness by refraining from alcoholic beverages in worship services.